Challenges Associated with Working and Studying as Expressed by Undergraduates in the University of Ilorin, Nigeria - ILORI, Oyedotun Dolapo; AKERELE, Patrick Oluwafemi (Ilorin Journal of Education, 2024)
The study examined challenges associated with working and studying as expressed by undergraduates in the university of Ilorin, Nigeria, using descriptive survey type. The study seems necessary to help students understand the integrities of work study and for school management to make work study more available for students. The study adopts a descriptive survey. The study covers all the faculties in University of Ilorin, Ilorin Kwara State, and the population for the study comprises all undergraduate students, the sample size is 380. The questionnaire that was used as instrument for the study was titled "Challenges Associated with Working and Studying Questionnaire" (CAWSQ) with reliability coefficient of 0.87. One research question was raised and two hypotheses were tested at 0.05 level of significance. Data was collected online using Toolbox data collector. The study concluded that the challenges associated with combining work and school vary as students advance from year one to the next phase, there is greater workload, as such highly skilled counsellor working in universities need to help students harness suitable resources and every academic support facility for the students. The study recommends that professional counsellors should endeavour to communicate the primary purpose of work study programme to university community which will not cause problem for students who are willing to engage in working and studying at the same time.